Adverbs Derivation from Nominatives and Participles in the Lithuanian Dialect of Gervėčiai - Vaičiulytė-Romančuk, Ona (Slavistica Vilnensis, 2009)
This article discusses several types of adverbs derived from nominatives and participles in the Lithuanian dialect of Gervėčiai. The main types of derivation are as follows: derivation with affixes, and adverbialisation of prepositional constructions and noun cases. The types of adverbs selected are typologically indiscrete or Lithuanian and mixed Slavonic.